Carbon based catalysts for the hydrodeoxygenation of lignin and related molecules: A powerful tool for the generation of non-petroleum chemical products including hydrocarbons. (November 2020) - Sharma, Vinit; Getahun, Tokuma; Verma, Minal; Villa, Alberto; Gupta, Neeraj
Abstract: Lignin has a complex aromatic framework that can be used to generate various aromatic compounds capable to replace chemicals (including hydrocarbon fuels) derived from unrefined oil. However, the selective cleavage of polymeric lignin to simpler molecules is a demanding task due to excessive oxygen content present in it. Hence, reducing the whole oxygen content from lignin by-products is necessary for their effective use. Hydrodeoxygenation is a process capable to reduce the overall oxygen content present in lignin with the support of hydrogen gas. Carbon materials deliver a good opportunity to design catalysts for hydrodeoxygenation by providing chemically inert surface and tunable functional groups to support the metal nanoparticles. The main objective of this work is to give an account on the use of carbon material supported heterogeneous catalysts for the HDO of lignin and related molecules for the synthesis of non-petroleum chemical products including hydrocarbons. Thus, this review presents a variety of carbon catalysts for performing the HDO reaction in lignin or its derivatives. The surface properties of the catalysts and mechanistic insights into the conversion with key active sites are provided, which will help the designing of new and effective catalysts for this biomass conversion. Graphical abstract: Image 1 Highlights: Hydrodeoxygenation of lignin mainly into hydrocarbons is presented with carbon based catalysts. Surface properties of carbon materials including nanocarbon based catalysts are summarized. Active metal sites used for HDO of lignin are presented. Mechanistic insight and pathways invovling different intermediates for the HDO reaction are discussed in detail. Aromatic and aliphatic molecules that can be derived from lignin are compiled.